Estimating the economic impact of the Sydney Olympic Games - John Madden; Matthew Crowe (European Regional Science Association (ERSA), 1998)
This paper employs a multiregional computable general equilibrium (CGE) model to examine the effects on the New South Wales and Australian economies of the 2000 Olympics. The Olympics are modelled over a 12-year period from 1994 to 2005, divided into three phases: (i) the Pre-Event phase, 1994 to 1999; (ii) the Event Year, 2000; and (iii) the Post-Event phase, 2001-2005. Construction of the Olympics venues and associated infrastructure is modelled as occurring in the first phase, while the operation of the Games (including ticketing) and Games tourism (i.e. visits by spectators, Games participants, etc.) is assumed to occur largely in the second phase. Induced tourism is modelled as occurring in all three phases. This latter (international visitor) effect relates to expected increased visitations to Sydney and other Australian destinations generated by heightened awareness of Australia via Olympics media coverage. The simulations are conducted under the assumption that the Games have a neutral effect in the long run on the budget of the Government of New South Wales (the Australian State hosting the 2000 Olympics) and on Australia?s balance of trade. For instance, the State Government finances the Olympics construction partly by crowding out other capital works, and partly from short-term debt that is paid off, by the end of the Event year, with Games revenues and with additional tax revenue flowing from the boost the Olympics has on the State?s tax base. The labour market is assumed to be slack in the Event year, but in the Pre-Event year increased labour demand is assumed to lead partly to an increase in real wages. Additional capital stock is put in place in the Pre-Games period, but it is assumed that industry capital stocks are fixed in the Event year. The Olympics capital stock is fully used in the Event year and in other industries fixed capital stocks leads to increased rates of return, and thus temporarily higher prices. The results of the simulations indicate that the Sydney Olympics should have a significant positive effect on the New South Wales and Australian economies. The present value of the impact on real GDP and real household consumption for Australia over the three phases of the Olympics is 6.1 billion (Australian dollars) and 2.7 billion respectively. However, virtually all of this gain occurs within New South Wales, with only a very small net effect on the other five state economies. Also while the effects are large in dollar terms, in percentage change terms the increases in New South Wales Gross State Product and real household consumption are only 0.36 and 0.22 per cent respectively in an average year of the twelve-year Olympics period.
Keywords: 330